Comparing two different doses of intravenous granisetron versus intravenous pethidine for prevention of shivering in patients undergoing spinal anaesthesia - Teoh, Jui Chang (2016)
Background: Post-anaesthesia shivering is physiologically and psychologically stressful event. Pethidine, which is commonly recognised as first-line therapy, can have several side effects such as sedative effects, nausea and vomiting. Granisetron has been proven in various studies for prevention of post-anaesthesia shivering at 40mcg/kg intravenously. To date, no study has demonstrated the minimum dose of granisetron to prevent post-anaesthesia shivering. This study compared two different dosages of intravenous granisetron versus pethidine for prevention of post-anaesthesia shivering. Methods: This was a prospective, randomized, double-blinded study. A total of 96 patients with ASA classification I and II, aged between 18 and 65 years old scheduled for orthopaedic lower limb surgery under spinal anaesthesia were recruited. Patients were randomly allocated to receive either intravenous (IV) granisetron 10mcg/kg (Group 1), IV granisetron 40mcg/kg (Group 2) or IV pethidine 0.4mg/kg (Group 3) before an intrathecal injection of 15 mg 0.5% hyperbaric bupivacaine. The incidence and severity of shivering with side effects of tested drugs were recorded. Results: The incidence of shivering associated with spinal anaesthesia in our study was not significant different amongst the 3 groups (p = 0.404). However, pethidine was associated with sedative effects when compared with granisetron (p < 0.001). Conclusions: IV granisetron at 10mcg/kg had similar efficacy when compared to both IV granisetron 40mcg/kg and IV pethidine 0.4mg/kg in preventing shivering during spinal anaesthesia for orthopaedic lower limb surgery.